DIFFERENTIATED LEARNING MODEL IN ISLAMIC RELIGIOUS EDUCATION TO REALIZE INCLUSIVE LEARNING AT LES ASIFA TUTORING INSTITUTION - Nabilla Sifa; Muhlisin Muhlisin; Rahmi Anekasari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The focus of adaptive teaching models has so far been dominated by formal school environments, while empirical analysis of their implementation in non-formal tutoring institutions remains very limited. This issue highlights the importance of reconstructing out-of-school pedagogical governance to equitably address the diversity of children's characteristics. This study aims to explore the implementation of a differentiated learning model in Islamic Religious Education (IS) to achieve inclusive student learning. The research steps were carried out using a descriptive qualitative approach through a structured phenomenological design. The actual data collection procedure was collected in-depth from five tutors and thirty-five students at the Les Asifa Tutoring Institute through field observations, interviews, and written documentation, which were then analyzed using thematic methods. The research findings indicate that the differentiation strategy successfully operated through flexible class classification based on student learning readiness, including small-group intervention classes, intensive classes, and advanced classes. This synergy proved effective in increasing emotional participation, intrinsic motivation, and self-confidence in children without any social discrimination. The main conclusion confirms that this teaching model successfully realized an inclusive ecosystem through substantive modifications to the content, process, and product aspects that were adaptive to individual needs. Tutoring practitioners are recommended to draft teaching modules based on mapping students' initial abilities on a regular basis to ensure the continued quality of contemporary educational processes. ABSTRAK Fokus model pengajaran adaptif sejauh ini masih didominasi oleh lingkungan sekolah formal, sedangkan analisis empiris mengenai penerapannya di lembaga bimbingan belajar non-formal masih sangat terbatas. Masalah tersebut memicu pentingnya rekonstruksi tata kelola pedagogis luar sekolah guna merespons keberagaman karakteristik anak secara adil. Penelitian ini bertujuan mengeksplorasi implementasi model pembelajaran diferensiasi dalam mata pelajaran Pendidikan Agama Islam untuk mewujudkan inklusivitas belajar siswa. Langkah-langkah penelitian dijalankan menggunakan pendekatan kualitatif deskriptif melalui desain fenomenologi yang terstruktur. Prosedur pengumpulan data aktual dihimpun secara mendalam dari lima tutor dan tiga puluh lima siswa di Lembaga Bimbingan Belajar Les Asifa melalui teknik observasi lapangan, wawancara, serta dokumentasi tertulis, yang selanjutnya dianalisis menggunakan metode tematik. Temuan penelitian menunjukkan bahwa strategi diferensiasi berhasil dioperasikan melalui pengklasifikasian kelas yang fleksibel berdasarkan kesiapan belajar siswa, meliputi kelas intervensi kelompok kecil, kelas intensif, hingga kelas unggulan. Sinergi ini terbukti efektif meningkatkan partisipasi emosional, motivasi intrinsik, serta rasa percaya diri anak tanpa adanya diskriminasi sosial. Simpulan utama menegaskan bahwa model pengajaran ini sukses merealisasikan ekosistem inklusif melalui modifikasi substansif pada aspek isi, proses, dan produk yang adaptif terhadap kebutuhan individu. Praktisi bimbingan belajar direkomendasikan menyusun draf modul ajar berbasis pemetaan kemampuan awal murid secara berkala demi menjamin keberlanjutan mutu proses edukasi kontemporer.